Comparative proteomic analysis on fruit ripening processes in two varieties of tropical mango (Mangifera indica) - Chin, Chiew Foan; Teoh, Ee Yang; Chee, Marcus Jenn Yang; Al-Obaidi, Jameel R.; Rahmad, Norasfaliza; Lawson, Tamunonengiyeofori (Springer, 2019)
Mango (Mangifera indica L.) is an economically important fruit. However, the marketability of mango is affected by the perishable nature and short shelf-life of the fruit. Therefore, a better understanding of the mango ripening process is of great importance towards extending its postharvest shelf life. Proteomics is a powerful tool that can be used to elucidate the complex ripening process at the cellular and molecular levels. This study utilized 2-dimensional gel electrophoresis (2D-GE) coupled with MALDI-TOF/TOF to identify differentially abundant proteins during the ripening process of the two varieties of tropical mango, Mangifera indica cv. ‘Chokanan’ and Mangifera indica cv ‘Golden Phoenix’. The comparative analysis between the ripe and unripe stages of mango fruit mesocarp revealed that the differentially abundant proteins identified could be grouped into the three categories namely, ethylene synthesis and aromatic volatiles, cell wall degradation and stress-response proteins. There was an additional category for differential proteins identified from the ‘Chokanan’ variety namely, energy and carbohydrate metabolism. However, of all the differential proteins identified, only methionine gamma-lyase was found in both ‘Chokanan’ and ‘Golden Phoenix’ varieties. Six differential proteins were selected from each variety for validation by analysing their respective transcript expression using reverse transcription-quantitative PCR (RT-qPCR). The results revealed that two genes namely, glutathione S-transferase (GST) and alpha-1,4 glucan phosphorylase (AGP) were found to express in concordant with protein abundant. The findings will provide an insight into the fruit ripening process of different varieties of mango fruits, which is important for postharvest management.